Validation of an analytical technique, distribution, and risk assessment of aliphatic and polycyclic aromatic hydrocarbons in surface sediments of the coastal and selected estuaries of Sarawak - Ebenezer Aquisman, Asare; Zaini, Assim; Rafeah, Wahi (Springer Nature, 2021)
This study explains a validation of an analytical technique, monitoring, and risk evaluation of hydrocarbons in surface sediments of the coastal and selected estuaries of Sarawak, Malaysia. The performance of an analytical methodology was validated for the evaluation of hydrocarbons in coastal and estuaries sediment samples. After the clean-up and separation process, GC-FID and GC-MS were used to quantify aliphatic and polycyclic aromatic hydrocarbon extracts, respectively. The suggested methodology is able to measure aliphatic and polycyclic aromatic hydrocarbons in samples at lower concentrations for example 10 ng/g. The precision of the technique was satisfactory as compared to 15% for most of the analytes. This method gives information concerning the distribution and characteristics of hydrocarbon contaminants in the coastal environment. In regard to monitoring and risk assessment, total n-alkane concentrations (C10–C33) varied from 96.63 to 367.28 ng/g dw. The lowest and highest nalkane content is observed at Santubong estuary (CZ10) and the coastal site CZ2, respectively. Simultaneously, the contents of ∑PAHs varied from 12.54 to 21.20 ng/g dw. The highest ∑PAH content is reported in the sediments of coastal site CZ8 (21.20 ng/g dw), whereas the lowest content is recorded in the sediments of coastal site CZ3 (12.54 ng/g dw). The outcome of the risk assessment suggested that there is no risk in all the studied locations. The findings from this study will help to understand the sources and possible risks of hydrocarbons in the coastal and estuary settings, and provide information for safeguarding human health and aquatic bodies in the studied area.